Halal products in Malaysia: a bibliometric analysis - Fadhlina, Anis; Mohamad Nor, Maryana (Rynnye Lyan Resources, 2024)
Malaysia is considered a pioneer in the halal industry and still leading in halal market products. In this study, a literature search was conducted using the Scopus database to study the trends of halal products in Malaysia and identify well-established products as well as emerging niches. The data extracted from the Scopus database were analysed and then visualized using VOSviewer to determine top authors, articles, sources and halal products. A total of 252 publications were identified using the “Halal product Malaysia” keyword. Based on the analysis, research on the halal product was observed to be initiated in 2005 with a total of 31 authors and 18 sources published more than 3 documents. The analysis of sources revealed that the Journal of Islamic Marketing was the most prolific source. The results showed that research on halal products in Malaysia was dominated by food which was critical to the halal industry. The research on food products focused on securing the supply chain as well as halal certification. The bibliometric analysis also showed that Halal cosmetics is an emerging product in the halal industry with Islamic marketing as its tool for product commercialization especially in the last five years.